Factors Affecting Poor Strategy Implementation - Pella, Muh. Darmin Ahmad; Sumarwan, Ujang; Daryanto, Arief; Kirbrandoko, . (Gadjah Mada International Journal of Business, 2013)
Research on strategy implementation has been developed for three decades, yet only a few studies focus on factors affecting poor strategy implementation. This research evaluates the influence of strategy implementation problems on strategy implementation success and firm performance. This survey was conducted in 60 Indonesian companies and the data were statistically analysed using Structural Equation Modeling Partial Least Square (SEM PLS). The results show significant influence of strategy implementation problems on the degree of successful strategy implementation and perceived firm performance. The seven major obstacles that have impact on poor strategy implementation are: problems related to corporate scorecard, key performance indicators, information technology, competence, performance appraisal, strategy management office, and financial support.